2014
DOI: 10.1590/brag.2014.024
|View full text |Cite
|
Sign up to set email alerts
|

Plantio direto de alface americana sobre plantas de cobertura dessecadas ou roçadas

Abstract: ResumoO objetivo deste trabalho foi avaliar o plantio direto de alface americana no verão sobre plantas de cobertura dessecadas ou roçadas em cultivos sucessivos. O trabalho foi desenvolvido no município de Álvares Machado, São Paulo, Brasil. O delineamento experimental foi em blocos ao acaso, dispostos em parcelas subdivididas, com quatro repetições. O fator da parcela principal foram dois manejos das plantas de cobertura (dessecadas com herbicida ou roçadas) e as subparcelas, seis espécies de plantas de cobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 15 publications
2
6
0
13
Order By: Relevance
“…The effects promoted by millet straw in this study coincide with the results found by Hirata et al (2014), who obtained excellent responses with virtually total control of weeds by the straw of millet (P. glaucum).…”
Section: Resultssupporting
confidence: 90%
“…The effects promoted by millet straw in this study coincide with the results found by Hirata et al (2014), who obtained excellent responses with virtually total control of weeds by the straw of millet (P. glaucum).…”
Section: Resultssupporting
confidence: 90%
“…In order to minimize the effects of soil contraction with expansive clays, mulching with vegetal remains is used to reduce the evaporation of water available to plants, obtaining greater conservation of soil moisture and reducing water consumption (FREIRE et al, 2011), in addition to reducing the direct interception of solar rays and promoting low competition for spontaneous plants (HIRATA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Na análise do plantio direto de alface americana sobre plantas de cobertura realizada por Hirata et al (2014), a cobertura do solo também influenciou a produtividade da cultura da alface, no primeiro ano de cultivo. Segundo os autores, a cobertura do solo com mucuna (Mucuna pruriens) resultou em maior produtividade da alface no primeiro ano de cultivo, devido ao excesso de palha das demais coberturas (Cajanus cajan cv.…”
Section: Tratamentosunclassified